(untitled) (Al-Academy, 2020)
The study entitled (Anthropometric Treatments of the Study Seat Units Used in Elementary stages) highlighted the relations between the sizes of dimensions of the study seats and the different anthropometric sizes of the students. The study problem is manifested in the following question: what are the anthropometric treatments used in the design of the study seats in the elementary stages? The research aims at finding design treatments for the anthropometric variables of the study seats used in the elementary stages, because the study seats have to do with preserving students health and safety through providing an ideal seating mechanism compatible with the anthropometric variables which enhances comfort, safety and focus in the most important educational institution, in which the students spend half of their time, i.e. the school. The descriptive approach has been adopted in the analysis of the samples which represented (3. 33 %) of the research community. The results have shown that the design processes of the formal formations for the study seat units are (100%) incompatible with the anthropometric dimensions in the seat bench body (depth of the seat) in the samples (1-2) which resulted in discomfort and weakness in performance. The lack of backrests in study seat units led to poor functional effectiveness, and they lack safety and security for the students in the three samples with (100%). The study came up with important conclusions that the designer’s prior knowledge of the anthropometric measures of the student contributes to activating the performance side( the functional and the formal) in order to achieve the integration feature for the student and the study seat units.